Interleukin-15 signaling in HIF-1α regulation in natural killer cells, insights through mathematical models - Coulibaly, Anna; Bettendorf, Anja; Kostina, Ekaterina; Figueiredo, Ana Sofia; Velásquez, Sonia Y.; Bock, Hans Georg; Thiel, Manfred; Lindner, Holger A.; Barbarossa, Maria Vittoria (Frontiers in immunology, 2019)
Natural killer (NK) cells belong to the first line of host defense against infection and cancer. Cytokines, including interleukin-15 (IL-15), critically regulate NK cell activity, resulting in recognition and direct killing of transformed and infected target cells. NK cells have to adapt and respond in inflamed and often hypoxic areas. Cellular stabilization and accumulation of the transcription factor hypoxia-inducible factor-1alpha (HIF-1alpha) is a key mechanism of the cellular hypoxia response. At the same time, HIF-1alpha plays a critical role in both innate and adaptive immunity. While the HIF-1alpha hydroxylation and degradation pathway has been recently described with the help of mathematical methods, less is known concerning the mechanistic mathematical description of processes regulating the levels of HIF-1alpha protein and mRNA. In this work we combine mathematical modeling with experimental laboratory analysis and examine the dynamic relationship between HIF-1alpha mRNA, HIF-1alpha protein and upstream signaling events mediating their regulation by IL-15 in NK cells from human blood. We propose a system of nonlinear ordinary differential equations with positive and negative feedback loops for describing the complex interplay of HIF-1alpha regulators. The experimental design is optimized with the help of mathematical methods and numerical optimization techniques yield reliable parameter estimates. The mathematical model allows for the investigation and prediction of HIF-1alpha stabilization under different inflammatory conditions and provides a better understanding of mechanisms mediating cellular enrichment of HIF-1alpha. Thanks to the combination of in vitro experimental data and in silico predictions we identified the mammalian target of rapamycin (mTOR), the nuclear factor-kappaB (NF-kB) and the signal transducer and activator of transcription 3 (STAT3) as central regulators of HIF-1alpha accumulation. We hypothesize that the regulatory pathway proposed here for NK cells can be extended to other types of immune cells. Understanding the molecular mechanisms involved in the dynamic regulation of the HIF-1alpha pathway in immune cells is of central importance to the immune cell function and could be a promising strategy in the design of treatments for human inflammatory diseases and cancer.